Eckerite, Ag2CuAsS3, a new Cu-bearing sulfosalt from Lengenbach quarry, Binn valley, Switzerland: description and crystal structure. (2nd January 2018) - Bindi, L.; Nestola, F.; Graeser, S.; Tropper, P.; Raber, T.
Abstract: Eckerite, ideally Ag2 CuAsS3, is a new mineral from the Lengenbach quarry in the Binn Valley, Valais, Switzerland. It occurs as very rare euhedral crystals up to 300 μm across associated with realgar, sinnerite, hatchite, trechmannite and yellow, fibrous smithite. In thick section eckerite is opaque with a metallic lustre and shows a dark orange-red streak. It is brittle; the Vickers hardness (VHN25 ) is 70 kg/mm 2 (range: 64–78) (Mohs hardness of ∼2½–3). In reflected light, eckerite is moderately bireflectant and weakly pleochroic from light grey to a slightly bluish grey. Internal reflections are absent. Under crossed nicols, it is weakly anisotropic with greyish to light blue rotation tints. Reflectance percentages for R min and R max are 27.6, 31.7 (471.1 nm), 22.8, 26.1 (548.3 nm), 21.5, 24.5 (586.6 nm) and 19.4, 22.3 (652.3 nm), respectively. Eckerite is monoclinic, space group C 2/ c, with a = 11.8643(3), b = 6.2338(1), c = 16.6785(4) Å, β = 110.842(3)°, V = 1152.81(5) Å 3, Z = 8. The crystal structure [ R 1 = 0.0769 for 1606 reflections with F o > 4σ( F o )] is topologically identical to that of xanthoconite and pyrostilpnite. In the structure, AsS3 pyramids are joined by AgS3 triangles to form double sheets parallel to (001); the sheets are linked by Cu(Ag) atoms in a quasi-tetrahedral coordination. Among the three metals sites, Ag2 is dominated by Cu. The mean metal–S distances reflect well the Ag ↔ Cu substitution occurring at this site. The eight strongest powder X-ray diffraction lines [ d in Å ( I / I 0 ) (hkl)] are: 3.336 (70) (312); 2.941 (100) (314, 114); 2.776 (80) (400, 206); 2.677 (40) (312); 2.134 (50) (421); 2.084 (40) (208, 206); 2.076 (40) (420); 1.738 (40) (228, 226). A mean of five electron microprobe analyses gave Ag 52.08(16), Cu 11.18(9), Pb 0.04(1), Sb 0.29(3), As 15.28(11), S 20.73(13), total 99.60 wt.%, corresponding, on the basis of a total of 7 atoms per formula unit, to Ag2.24 Cu0.82 As0.94 Sb0.01 S2.99 . The new mineral has been approved by the International Mineralogical Association Commission on New Minerals, Nomenclature and Classification (2014–063) and named for Markus Ecker, a well known mineral expert on the Lengenbach minerals for more than 25 years.